Asian paleoanthropology from Africa to China and beyond - Norton, Christopher J. (Christopher John).; Braun, David R. (David Royce).; SpringerLink (Online service). (Dordrecht Springer, 2011)
This volume brings together a group of authors that address the question of the first out of Africa into Asia c. 2 Ma. The scope of the book is comprehensive as it covers almost every major region of Asia. The primary goal of this volume is to provide an updated synthesis of the current state of the Asian paleoanthropological and paleoenvironmental records. Papers include detailed studies of the theoretical constructs underlying the move out of Africa, including detailed reconstructions of the paleoenvironment and possible migration routes. Other papers detail the Plio-Pleistocene archaeological and hominin fossil records of particular regions.
1. Asian paleoanthropology: An introduction -- 2. The colonization of Savannahstan: issues of timing(s) and patterns of dispersal across Asia in the Late Pliocene and Early Pleistocene -- 3. On the road to China: The environmental landscape of the Early Pleistocene in western Eurasia and its implication for the dispersal of Homo -- 4. East Africa and East Asia: Comparisons of the earliest archaeological evidence -- 5. Inter-continental variation in Acheulean bifaces -- 6. Cranial shape in Asian Homo erectus: geographic, anagenetic, and size-related variation -- 7. Rethinking the Palearctic-Oriental biogeographic boundary in Quaternary China -- 8. The history of hominin occupation of Central Asia in review -- 9. Core-and-flake assemblages of India -- 10. South Asia as a geographic crossroad: Patterns and predictions of hominin morphology in Pleistocene India -- 11. Cranial morphology and variation of the earliest Indonesian hominins -- 12. Central-East China - a Plio-Pleistocene dispersal corridor: The current state of evidence for hominin occupations -- 13. The earliest hominin occupations in the Nihewan Basin of northern China: recent progress in field investigations -- 14. Peopling in the Korean Peninsula -- 15. When were the earliest hominin migrations to the Japanese Islands?
Electronic reproduction.
Keywords: Human evolution -- Asia; Paleoanthropology -- Asia; Human ecology -- Asia; Electronic books